Highly Efficient Photocatalytic Hydrogen on CoS/TiO2 Photocatalysts from Aqueous Methanol Solution. (16th September 2018) - Niu, Yu; Li, Fuying; Yang, Kai; Wu, Qiyou; Xu, Peijing; Wang, Renzhang
Abstract : The photocatalyzed water splitting reaction in aqueous methanol solution is an efficient preparation method for hydrogen and methanal under mild conditions. In this work, metal sulfide-loaded TiO2 photocatalysts for hydrogen and methanol production were synthesized by hydrothermal method (180°C/12 h) and characterized by X-ray diffraction (XRD), UV-visible diffuse reflectance spectroscopy (DRS), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX). The crystal structures of the samples are the typical anatase phase of TiO2 and exhibit a spherical morphology. When TiO2 was loaded with CoS, ZnS, and Bi2 S3, respectively, the resulting catalysts showed photocatalytic activities for water decomposition to hydrogen in aqueous methanol solution under 300 W Xe lamp irradiation. Among the photocatalysts with various compositions, the 20 wt% CoS/TiO2 sample with a 2.1 eV band gap showed the maximum photocatalytic activity for the photocatalytic reaction, which indicated that CoS improved the separation ratio of photoexcited electrons and holes. The enhanced activity can be attributed to the intimate junctions that are formed between CoS and TiO2, which can reduce the electron-hole recombination. The production rate of hydrogen with 20 wt% CoS/TiO2 photocatalyst was about 5.6 mmol/g/h, which was 67 times higher than that of pure TiO2 . The formation rate of HCHO was 1.9 mmol/g/h with 98.7% selectivity. Moreover, the CoS/TiO2 photocatalyst demonstrated good reusability and stability. In the present study, it is demonstrated that CoS can act as an effective cocatalyst to enhance the photocatalytic hydrogen and methanal production activity of TiO2 . The highly improved performance of the CoS/TiO2 composite was mainly ascribed to the efficient charge separation.